Deformation Monitoring in Steel Arch Bridges Through Close-Range Photogrammetry and the Finite Element Method - Tasci, L. (Springer, 2015)
Deformation measurements are performed periodically to prevent death and injuries in case of the damage or collapse of manmade structures such as dams, tunnels, bridges, high-rise buildings, and other natural landslide regions. Deformations and displacements in such structures can occur if structures are not built on solid ground and they are subjected to huge static loadings, which causes hazardous shaking due to the motion of the ground beneath. To reduce losses, it is very important to make continuous observations using various measurement methods to detect changes and to analyze the scales of these changes using various analysis techniques. The aim of this study is to determine the behavior of a steel arch bridge under a static load by measuring and analyzing potential deformations and displacements using four different measurement methods. The graphs depicting the result of each measurement method show that the results of the four different measurement methods coincide with each other.
Keywords: Bridge; Deformation; Photogrammetry; Finite Element Method